2007
DOI: 10.1007/s00038-007-6035-8
|View full text |Cite
|
Sign up to set email alerts
|

Caesarean sections and breastfeeding initiation among migrants in Switzerland

Abstract: Our data confirms inequalities in reproductive health outcomes and responses to health promotion programmes among migrant women in Switzerland. These differences are dependent on educational level and on the mothers' nationality. The large variation suggests that different trans-national experiences play some role in health-related decision-making and access to health care. This should be considered when planning health promotion programs and the individual counselling of pregnant mothers in Switzerland.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
56
2
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(69 citation statements)
references
References 34 publications
7
56
2
2
Order By: Relevance
“…Our results agree with those from studies in other European countries identifying a higher prevalence of breastfeeding in immigrants as a whole than in nonimmigrants (De Amici et al, 2001;Merten et al, 2007;Hawkins et al, 2008). One study in London (Evans et al, 1976) (50 Asian mothers) and another more recent in France (Rovillé-Sausse, 2005) (60 Asian mothers) have also described a drastic reduction in the establishment of breastfeeding among North-Asian immigrants.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…Our results agree with those from studies in other European countries identifying a higher prevalence of breastfeeding in immigrants as a whole than in nonimmigrants (De Amici et al, 2001;Merten et al, 2007;Hawkins et al, 2008). One study in London (Evans et al, 1976) (50 Asian mothers) and another more recent in France (Rovillé-Sausse, 2005) (60 Asian mothers) have also described a drastic reduction in the establishment of breastfeeding among North-Asian immigrants.…”
supporting
confidence: 92%
“…Initiation of breastfeeding in hospital is considered a quality care indicator during the perinatal period. Research in Europe has shown that, in general, the frequency of breastfeeding initiation is high in immigrants, although maintenance of this type of nourishment decreases in parallel to the time of residence in the new country (De Amici et al, 2001;Merten et al, 2007; Hawkins et al, 2008). Spain is among the 10 countries receiving the largest number of international migrants.…”
mentioning
confidence: 99%
“…Longitudinal studies of preterm babies born after unnecessary medical intervention can give further light to these suggestions and to the understanding of the evolutionary significance of plasticity and its applications in public health. It has also been demonstrated that all children who are born preterm, with low birth weight or by Caesarean section are at increased risk of missing maternal breastfeeding (Merten et al, 2007;Montero, 2009) and all the known benefits associated with it, including those leading to better biological outcomes later in life (Haines and Kintner, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…IJPH Profi le 1 (Annaheim et al 2007; Merten et al 2007) 2 (Eichhorn et al 2007) 3 (Yunis et al 2007) 4 (Máchová et al 2007) 5 (Staehelin et al 2007) 6(Merten et al 2007) …”
mentioning
confidence: 99%